Desenvolvimento de aplicações para dispositivos móveis baseados em plataformas cruzadas - Wottrich, Tiago (2016)
More than ever “time is money”, and because of this point of view the concept of alternative mobile development fits well. It’s not necessary anymore having to rewrite the same code in different languages for each platform you wish to achieve, and because of that you gain productivity and saves money. This project has the objective of contextualize this kind of development and also the main tools available in the market. Lastly a prototype will be built making use of one of the technologies studied.